Methylene blue-based near-infrared activatable probes for bioimaging. (March 2023) - Li, Songjiao; Wang, Peipei; Yang, Ke; Liu, Ying; Cheng, Dan; He, Longwei
Abstract: A near-infrared methylene blue-based fluorogenic probe with an on/off activation ability has emerged as an important means to detect and monitor biological analytes and to understand the biological processes involved in understanding these analytes within cells and organisms. By using biomarker-activated methylene blue-based probes, it is possible to produce more precise results with a lower risk of photodamage to biological samples and fewer biological interferences in the background. This brief review aims to give a rigorous but concise account of recent developments in activatable methylene blue-based fluorogenic probes by reporting the significant accomplishments in that field. Several strategies for detecting and imaging disease-related biomarkers (such as ROS, RRS, enzymes, ions, and other related species) have been discussed and analyzed. Additionally, methylene blue-based fluoroscopic probes are emphasized for use in developing new methods to detect and image biomarkers to address potential challenges and opportunities. Highlights: Recent progresses in methylene blue-based fluorescent probes are reviewed. The design strategies of methylene blue-based probes for various analytes and drug delivery systems have been discussed. The bio-imaging with methylene blue-based probes in cells and in vivo are presented. The challenges and opportunities for design methylene blue-based probes are discussed and forecasted.